INTERCULTURAL COMPETENCE: DEVELOPING INTERCULTURAL UNDERSTANDING AND COMMUNICATION SKILLS IN THE CONTEXT OF MODERN EDUCATION (Konferensiyalar | Conferences, 2024)
In today's interconnected world, the ability to navigate diverse cultural landscapes is paramount. This article explores the significance of intercultural competence development within the framework of modern education. By examining the challenges and opportunities associated with fostering intercultural understanding and communication skills, this study sheds light on effective strategies and best practices for educators and learners alike. Drawing on theoretical frameworks and practical examples, the article underscores the importance of promoting empathy, respect, and open-mindedness as foundational principles for cultivating intercultural competence. Through a comprehensive analysis of current trends and research findings, this article offers insights into how educational institutions can adapt their curricula and teaching methodologies to better prepare students for global citizenship in the 21st century.